The Islamic and conventional bank patronage factors of Small and Medium Enterprises (SMEs) / Koe Wei Loon, Nur Afizah Muhamad Arifin and Idris Osman - Wei Loon, Koe; Muhamad Arifin, Nur Afizah; Osman, Idris (2010)
In the present day's world, individuals as well as public and private institutions can hardly operate well without the banking institutions. The "dual banking system" in Malaysia has inevitably caused both the conventional banks and Islamic banks to face a stiffer market condition. Moreover, under the Ninth Malaysia Plan, Malaysia seeks to position itself as a global hub for Islamic financial products and services. As such, banks are facing greater challenges compared to the past. Thus, the understanding of what factors that are deemed to be important for customers, specifically small and medium enterprises (SMEs) in selecting a bank is crucial to the competitive survival of a bank. This study aims to investigate the patronage factors for banks among SMEs and also verify the differences of patronage factors between SMEs opting for conventional banks and Islamic banks. A total of 103 SMEs in Melaka were surveyed by using a self-administered questionnaire to determine their patronage factors for banks. Both SMEs that have opted for conventional banks and Islamic banks considered the financial return and bank's service factors as the most important factors in deciding which bank to patronize. In addition, the results from independent t-test revealed that significant differences were found in 13 patronage factors for SMEs opting for conventional banks and Islamic banks, which included the religion factor. Recommendations for bank operators, policy makers and future research have also been put forth in this study.